2023
DOI: 10.1111/liv.15601
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish facilitate non‐alcoholic fatty liver disease research: Tools, models and applications

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a metabolic-associated fatty liver disease (MAFLD) that is not related to alcohol intake. NAFLD is the most prevalent liver disease; it is estimated to affect almost 2 billion people globally, and the burden is expected to grow in the coming decades. 1 The main pathological feature of NAFLD is defined as steatosis occurring in more than 5% of hepatocytes. 2 NAFLD appears as simple excessive liver fat accumulation in the early stage and gradually exhibits hepatocellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 134 publications
0
11
0
Order By: Relevance
“…Their small size and translucent nature make them an ideal model organism to manipulate and observe. These attributes make them very attractive to study a variety of liver diseases 2 and underpins the significance of the present contribution by Chang et al 1 The authors elegantly discussed how the various genetic variants of the zebrafish model can be used to readily interrogate the complex nature of various biomolecular processes involved in non-alcoholic fatty liver disease (NAFLD).…”
Section: E T T E R T O T H E E D I T O R Zebrafish: An Emerging and E...mentioning
confidence: 91%
See 1 more Smart Citation
“…Their small size and translucent nature make them an ideal model organism to manipulate and observe. These attributes make them very attractive to study a variety of liver diseases 2 and underpins the significance of the present contribution by Chang et al 1 The authors elegantly discussed how the various genetic variants of the zebrafish model can be used to readily interrogate the complex nature of various biomolecular processes involved in non-alcoholic fatty liver disease (NAFLD).…”
Section: E T T E R T O T H E E D I T O R Zebrafish: An Emerging and E...mentioning
confidence: 91%
“…The review article by Chang et al in the May issue of Liver International highlights two important research topics in hepatic biology and pathobiology. 1 Firstly, the overall strengths of the zebrafish model for biomedical research, and secondly the increasing focus and use of zebrafish as an alternative model to those conventionally used in liver research (e.g. cultured cells and rodent models).…”
Section: E T T E R T O T H E E D I T O R Zebrafish: An Emerging and E...mentioning
confidence: 99%
“…Developing zebrafish is a well-established model for the study of lipid metabolism and liver diseases. The transparency of zebrafish larvae and the physiological similarities of their digestive system to that of mammals make them useful for studying lipid transport, energy homeostasis, and organ development. , …”
Section: Introductionmentioning
confidence: 99%
“…
We thank Shami et al for their commentary 1 on our recent publication. 2 Based on their expertise in correlative microscopy, Shami et alpointed out that the hepatic cellular makeup and ultrastructure in zebrafish are notably different from humans and suggested that caution should be taken when interpretating small-animal data which may have translational implications. 1 Indeed, our review acknowledged that most, but not all, major types of liver cells were identified in zebrafish.
…”
mentioning
confidence: 99%
“…We thank Shami et al for their commentary 1 on our recent publication. 2 Based on their expertise in correlative microscopy, Shami et al…”
mentioning
confidence: 99%